2020
DOI: 10.3389/fmed.2020.00482
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Anti-malarial Drugs (Chloroquine and Hydroxy-Chloroquine) in Treatment of COVID-19 Infection: A Systematic Review and Meta-Analysis

Abstract: Background: Anti-malarial drugs inhibit coronaviruses in-vitro. Few published studies have evaluated the safety and efficacy of these drugs in the treatment of COVID-19 infection. Materials and Methods: This is a systematic review and meta-analysis of clinical trials and observational studies. Major database searches were carried out up until June 5, 2020. Participants admitted with RT-PCR-confirmed SARS Cov-2 (COVID-19) infection were included. The "Intervention group" received anti-malarial drugs with or wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 48 publications
0
30
0
3
Order By: Relevance
“…However, as they are largely based on the sometimes heavily biased data of the studies discussed above, one might still doubt a causal inference. The data of azithromycin monotherapy have not been pooled, and of the three meta-analyses that directly compared hydroxychloroquine with azithromycin versus hydroxychloroquine alone, only Das et al 77 found a significantly increased mortality with the addition of azithromycin. Interestingly, not cardiac adverse events but rather the development of severe disease was an outcome associated with the addition of azithromycin to hydroxychloroquine.…”
Section: Rationale For Azithromycin Use In Covid-19mentioning
confidence: 99%
“…However, as they are largely based on the sometimes heavily biased data of the studies discussed above, one might still doubt a causal inference. The data of azithromycin monotherapy have not been pooled, and of the three meta-analyses that directly compared hydroxychloroquine with azithromycin versus hydroxychloroquine alone, only Das et al 77 found a significantly increased mortality with the addition of azithromycin. Interestingly, not cardiac adverse events but rather the development of severe disease was an outcome associated with the addition of azithromycin to hydroxychloroquine.…”
Section: Rationale For Azithromycin Use In Covid-19mentioning
confidence: 99%
“…Nowadays, there are increasing data reporting evidence of the ineffectiveness of CQ and HCQ in improving the prognosis or shorten the clinical course of COVID-19 (Gao et al 2020a;Horby et al 2020;Kashour et al 2020;Lammers et al 2020). Also, some reports highlight the severe risks, including death, when CQ is used in high dose and the potentially detrimental consequences of rapid dissemination of over-interpreted data of its efficacy (Das et al 2020;Ektorp 2020;Kim et al 2020;Touret and de Lamballerie 2020). In a recent report, Junqueira and Rowe highlighted the heterogeneous and insufficient approaches of early randomized control trials (RCTs) of the COVID-19 pandemic to measure CQ or HQ's effectiveness and safety relevant to patients and clinical practice and the urgent need for well-designed high-quality RCTs (Junqueira and Rowe 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Supply issues of HCQ for SLE patient have since luckily resolved, following clinical trials in hospitalized COVID-19 patients, including a randomized controlled trial and three large observational studies, that failed to demonstrate benefit [ 58 ]. Furthermore, HCQ use in combination with azithromycin was associated with increased mortality due to cardiac arrhythmias in this population [ 58 , 59 ]. Congruent to those results, observational studies in patients with SLE and other AIRDs and concurrent COVID-19 did not support a protective effect of HCQ against COVID-19 infection or hospitalization [ 28 , 30 , 32 , 35 •, 40 , 45 , 47 •, 60 , 61 ].…”
Section: Immune Suppressive Treatments For Sle and Covid-19mentioning
confidence: 99%
“…HCQ remains the cornerstone of therapy in patients with SLE, associated with decreased risk of flare, reduced longer-term morbidity and mortality, and improved pregnancy outcomes [57]. Supply issues of HCQ for SLE patient have since luckily resolved, following clinical trials in hospitalized COVID-19 patients, including a randomized controlled trial and three large observational studies, that failed to demonstrate benefit [58]. Furthermore, HCQ use in combination with azithromycin was associated with increased mortality due to cardiac arrhythmias in this population [58,59].…”
Section: Immune Suppressive Treatments For Sle and Covid-19mentioning
confidence: 99%